Enhancing MSMEs Business Growth: Exploring Market Orientation and Innovation Capability as Catalysts - Sakinah, Meidina Putri; Danial, R Deni Muhammad; Ramdan, Asep Muhamad (Edueksos Jurnal Pendidikan Sosial & Ekonomi, 2024)
This study aims to analyze the effect of market orientation on business growth of fashion MSMEs (Micro, Small and Medium Enterprises) in Sukabumi City, with innovation capability as the mediating variable. The focus of this study is to understand the extent to which market orientation affects innovation capability and business growth, and how innovation capability mediates the relationship. The research method used was quantitative with a causal descriptive approach. The study population consisted of 4,380 fashion MSMEs in Sukabumi City, with 200 MSMEs selected as samples through purposive sampling technique. Data was collected using questionnaires, literature study, and documentation. Data analysis was conducted using Structural Equation Modeling (SEM) with the help of AMOS 22 program. The results showed that market orientation has a positive and significant influence on innovation capability, indicated by the Critical Ratio (C.R) value of 0.674 and probability of 0.000. In addition, market orientation also has a positive and significant effect on business growth, with a C.R value of 0.839 and a probability of 0.000. Innovation capability is also found to have a significant influence on business growth, with a C.R value of 0.155 and a probability of 0.000. The mediation analysis results show that the effect of market orientation on business growth is stronger through innovation capability than its direct effect, as evidenced by the Sobel test value of 11,216, exceeding the z-table value of 1,969. Thus, the conclusion of this study emphasizes the importance of developing innovation capability in line with effective market orientation for fashion MSMEs in Sukabumi City to achieve optimal business growth.Keywords: Market Orientation; Innovation Capability; Business Growth; Fashion MSMEs.